2019
DOI: 10.1111/febs.15077
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic characterisation of Erv1, a key component for protein import and folding in yeast mitochondria

Abstract: Yeast (Saccharomyces cerevisiae) essential for respiration and viability 1 (Erv1; EC number http://www.chem.qmul.ac.uk/iubmb/enzyme/1/8/3/2.html), a member of the flavin adenine dinucleotide‐dependent Erv1/ALR disulphide bond generating enzyme family, works together with Mia40 to catalyse protein import and oxidative folding in the mitochondrial intermembrane space. Erv1/ALR functions either as an oxidase or cytochrome c reductase by passing electrons from a thiol substrate to molecular oxygen (O2) or cytochro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 45 publications
(63 reference statements)
1
16
0
Order By: Relevance
“…Next, the effects of the liposomes on the Erv1 oxidase activity were investigated using oxygen consumption analysis ( Figure 4 A), as described previously [ 23 , 36 ]. As shown at the beginning of Figure 4 A, there was no oxygen consumption by DTT in the absence of Erv1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, the effects of the liposomes on the Erv1 oxidase activity were investigated using oxygen consumption analysis ( Figure 4 A), as described previously [ 23 , 36 ]. As shown at the beginning of Figure 4 A, there was no oxygen consumption by DTT in the absence of Erv1.…”
Section: Resultsmentioning
confidence: 99%
“…Erv/ALR enzymes can act as an oxidase by passing electrons to molecular oxygen and reducing oxygen to hydrogen peroxide, or as a cytochrome c reductase by passing electrons to oxidized cytochrome c ( Figure 1 A). Enzyme kinetic studies revealed that different Erv1/ALR enzymes have different oxidase and cytochrome c reductase activities [ 17 , 21 , 22 , 23 ]. While both yeast Erv1 [ 23 ] and human ALR [ 21 ] seem to prefer cytochrome c more than molecular oxygen as an electron acceptor, the ratio of relative cytochrome c reductase to oxidase activity is quite different for these enzymes, with 15 for yeast Erv1 [ 23 ] and 107 for human ALR [ 21 ], as ALR uses oxygen poorly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon mitochondrial protein import, Mia40 acts as an oxidoreductase interacting with the substrate proteins directly and transfers a disulphide bond to the substrates via the formation of intermolecular disulphide linked complexes . The reduced Mia40 is then re‐oxidised by Erv1 (http://www.chem.qmul.ac.uk/iubmb/enzyme/EC1/8/3/2.html) for regeneration, and reduced Erv1 can be re‐oxidised by molecular oxygen or oxidised cytochrome c .…”
Section: Introductionmentioning
confidence: 99%
“…The electrons are then transferred to the active‐site (proximal) disulphide via formation of an intermediate disulphide (Fig. C, C33’‐C130), the cofactor FAD, and then in turn the reduced Erv1 can be re‐oxidised by transferring electrons to molecular oxygen (O 2 ) or cytochrome c for regeneration . Thus, there are three redox‐active centres in Erv1, the shuttle disulphide (C30‐C33), active‐site (proximal) disulphide (C130‐C133) and the FAD cofactor.…”
Section: Introductionmentioning
confidence: 99%